Sex-specific NLRP3 activation in neutrophils promotes neutrophil recruitment and NETosis in the murine model of diffuse alveolar hemorrhage - Jarrot, Pierre-André; Kim, Jiyoun; Chan, William; Heger, Lukas; Schommer, Nicolas; Cunin, Pierre; Silva, Camila M. S.; Robert, Stéphane; Nigrovic, Peter A.; Ewenstein, Bruce; Wagner, Denisa D. (Frontiers in Immunology, 2024)
ObjectivesDiffuse alveolar hemorrhage (DAH) is a life-threatening complication of systemic lupus erythematosus and small vessel vasculitis. We previously showed that neutrophil extracellular traps (NETs) were associated with the pathogenesis of pristane-induced DAH and demonstrated that neutrophil NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome assembly participated in NET generation under sterile stimulation. We investigated whether NLRP3 inflammasome assembly in neutrophils may drive pulmonary NETosis in a mouse model of pristane-induced DAH.MethodsC57BL/6J mice received a single intraperitoneal injection of 0.5mL of pristane. Neutrophil NLRP3 inflammasome assembly and NETs were characterized by immunofluorescence staining of apoptosis-associated speck-like protein a CARD (ASC), co-staining of DNA, and citrullinated histones, respectively. Clinical status of mice was assessed 11 days after pristane injection by measurement of arterial oxygen saturation and of weight loss; severity of lung injury was determined using a quantification score from hematoxylin-eosin-stained slides.ResultsPristane induced ASC speck formation in neutrophils and we confirmed that NLRP3 inflammasome was involved in NET generation after pristane stimulation in vitro. NLRP3 deficiency reduced the severity of pristane-induced DAH in female, but not male mice. Interestingly, NLRP3 deficiency reduced the number of neutrophils and NETs in the lungs of females compared to males.ConclusionsOur results suggest a link between female sex-specific NLRP3 inflammasome activation and subsequent pulmonary NETosis in the development of pristane-induced DAH. Therefore, we identified NLRP3 inflammasome as a potential new therapeutic target in this severe complication of pro-female autoimmune disease for which specific inhibitors of NLRP3 are currently developed.